PENGARUH THIRD PARTY FINANCING, FINANCING TO DEPOSIT RATIO DAN NON PERFORMING FINANCING TERHADAP RETURN ON ASSET DENGAN ISLAMIC INCOME RATIO SEBAGAI VARIABEL MODERASI - Husna, Nurul; Imsar, Imsar (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2023)
Research to determine the effect of TPF, FDR, and NPF on ROA with IsIR as a moderating variable .This research uses a quantitative approach. The research population is the financial reports of Islamic banks registered with the financial services authority and the sample chosen is the financial statements of Islamic banks in 2015-2021. The data analysis technique used is multiple linear regression analysis. The results of this research show that directly the Adjusted R Square (R2) value is 0.311 or 31.1%. In the Ttest, there is no significant or partial influence between TPF ROA. There is a significant and partial influence of FDR and NPF on ROA. Then in the Ftest it was discovered that TPF, FDR, and NPF had a big impact on ROA. Then in the moderate regression test it was discovered that TPF did not have a moderate effect on ROA, and FDR and NPF had a moderate effect on ROA. Future researchers are expected to be able to develop research related to other islamic bank financial reports.